Combustion characteristics and thermal enhancement of premixed hydrogen/air in micro combustor with pin fin arrays. (7th February 2020) - He, Ziqiang; Yan, Yunfei; Xu, Fulei; Yang, Zhongqing; Cui, Hongkun; Wu, Zhongda; Li, Lixian
Abstract: Targeted at improving the combustion stability and enhancing heat transfer in micro combustor, the combustion characteristics and thermal performance of micro combustor with pin fin arrays are numerically investigated by employing detail H2 /O2 reaction mechanism. It is shown that the micro combustor with staggered pin fin arrays exhibits the highest average temperature and heat flux of external wall, while the micro combustor with in-line pin fin arrays displays the most uniform temperature distribution of external wall. When the equivalence ratio is 1.1, all micro combustors exhibit the highest mean temperature and heat flux of external wall. The micro combustor materials with high thermal conductivity can not only improve the average temperature and heat flux of external wall, but also enhance heat transfer to the upstream which can preheat the mixed gas. Therefore, the materials with high thermal conductivity, such as red copper and aluminum, can make up for the nonuniform temperature distribution of micro combustor with staggered pin fin arrays, so as to realize uniform high heat flux output of external wall. Highlights: Micro combustor with staggered pin fin arrays exhibits the highest mean temperature and heat flux. Micro combustor with in line pin fin arrays shows the most uniform temperature distribution. All micro combustors exhibit highest average temperature when the equivalence ratio is 1.1. High thermal conductivity materials can realize uniform high heat flux output of external wall.